1991
DOI: 10.1007/bf00757259
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of nursing and rest home administrators toward deinstitutionalized elders with psychiatric disorders

Abstract: The administrators of 92 nursing homes and rest homes in western Massachusetts were surveyed on their experiences with elderly residents with a history of psychiatric hospitalization and their willingness to admit such individuals in the future. A majority of those who had admitted deinstitutionalized elders with chronic psychiatric disorders reported having experienced severe problems with them. Most of the problems involved the resident going into crisis or producing some highly disruptive behavior. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…First, given the current level of demand for nursing home care, many facilities still enjoy substantial flexibility in admitting different types of patients. Nursing home administrators may selectively avoid accepting patients with SMI 34 because they are worried about their socially inappropriate and many times dangerous behaviors, 2 and about the fact that their staff may not be competent enough to serve appropriately these patients. As a result, patients with SMI may be crowded out of the locally reputable nursing homes (ie, in terms of service quality) that are attractive to all prospective entrants; and they may be clustered into nursing homes that tend to house less desirable patients or locate in poor urban areas, have lower occupancy rates, provide less adequate services, and therefore be more inclined to accept these challenging patients.…”
Section: Discussionmentioning
confidence: 99%
“…First, given the current level of demand for nursing home care, many facilities still enjoy substantial flexibility in admitting different types of patients. Nursing home administrators may selectively avoid accepting patients with SMI 34 because they are worried about their socially inappropriate and many times dangerous behaviors, 2 and about the fact that their staff may not be competent enough to serve appropriately these patients. As a result, patients with SMI may be crowded out of the locally reputable nursing homes (ie, in terms of service quality) that are attractive to all prospective entrants; and they may be clustered into nursing homes that tend to house less desirable patients or locate in poor urban areas, have lower occupancy rates, provide less adequate services, and therefore be more inclined to accept these challenging patients.…”
Section: Discussionmentioning
confidence: 99%
“…The Deinstitutionalization of the Long‐Term Psychiatric Population . Lower‐tier facilities, particularly for‐profit facilities, are much more likely to serve the least desirable long‐term care residents, those with a history of psychiatric diagnoses (Mosher‐Ashley and O'Neill 1991). Many of these facilities may be serving the legacy of national policy directed at the deinstitutionalization of public mental hospitals over the last several decades (Mishara, Budd, and Dixon 1973).…”
mentioning
confidence: 99%
“…Nursing home administrators have cited concerns about potential behavior problems as a major factor affecting decisions about whether to admit individuals with serious mental illness (SMI), 6 but these administrators have also reported that residents with SMI are basically similar in general behavior to the general residential population. Facility administrators' inconsistent reports regarding the behaviors of residents with SMI raise the possibility that stigma and anxieties associated with SMI may affect admission and care decisions.…”
mentioning
confidence: 99%